The last step involves isolating \(x\). After reaching the equation \(-x = -6\), you would divide both sides by \(-1\) to solve for \(x\).
So, the correct answer is:
C. Divide both sides by -1 to get x = 6.
STEP 1: Use Distributive Property to get 3x-8=4x-14
STEP 2: Use Addition Property of Equality to get 3x = 4x-14+8
STEP 3: Combine Like Terms to get 3x = 4x-6
STEP 4: Use Subtraction Property of Equality to get 3x-4x= -6
STEP 5: Combine Like Terms to get (-x)=-6
What is the last step?
A.
Use Property of Equality to get x= (-6)
B.
Divide both sides by -1 to get x=6
C.
Divide both sides by -1 to get x= (-6)
D.
Use Multiplication Property of Equality to get x=6?
1 answer
The last step involves isolating \(x\). After reaching the equation \(-x = -6\), you would divide both sides by \(-1\) to solve for \(x\).
So, the correct answer is:
C. Divide both sides by -1 to get x = 6.